Description of the last instar larva of Peristicta aeneoviridis Calvert, 1909 (Odonata: Coenagrionidae) - Schröder, Noelia M.; Anjos-Santos, Danielle; Rippel, Camila G.; Pessacq, Pablo (Zootaxa, 2020)
The larva of Peristicta aeneoviridis Calvert, 1909 is described for the first time, based on material from Misiones Province, Argentina. It differs from the rest of the larvae described for the genus in the shape and coloration of caudal lamellae, femur setae, lacinia teeth and coloration patterns. Additions to the description of the larva of P. forceps Hagen in Selys, 1860 are included.